Fuzzy Logic Controller For Direct Current (DC) Motor Drive - Razali, Mohd Aminudin (UTeM, 2008)
Fuzzy logic controller is one type of intelligent controller. Fuzzy logic is much just like human operator or closer in spirit to human thinking and natural language than the traditional (classical) logical system. Basically, fuzzy logic have an effective means for describing the approximate, inexact natural or ambiguous of the reality problem. The fuzzy logic controller is useful for control processes that too complex to analyze by conventional quantitative techniques. This thesis is concern with fuzzy logic controller for DC Motor Drive. The first stages of this project are to study in detail the capability and ability of fuzzy logic compare to other controller that use in non-linear system like DC Motor Drive. The second stage is to design the fuzzy logic controller using the Fuzzy Logic Toolbox software in MATLAB. Lastly, designs the system apply the fuzzy logic controller in this system. The simulation work is done using a MATLAB/SIMULINK platform.